“I Have to Further My Studies Abroad”: Student Migration in Ghana - Kyei, Justice Richard Kwabena Owusu (2021)
The literature on migration intentions of university students and their decisions to travel abroad as student migrants is limited. This article outlines how the thought of student migration is created and nurtured. It investigates how facilitators and/or constraints influence the decision to migrate as students. Using a multi-sited approach, fieldwork in Ghana focused on prospective student migrants, while fieldwork in the Netherlands provided a retrospective perspective among student migrants. Life story interviews were adopted in the collection of data. In the minds of the respondents, there is a clear distinction between the idea of ‘migration’ and the idea of ‘student migration.’ The article concludes that childhood socialization shapes the idea of ‘migration’ that culminates in the thought of ‘student migration.’ Apart from studies, experiencing new cultures and networking are among the notableexpectations that inform the thought of studentmigration. Religiosity categorised as prayers and belonging to religious community is a cultural principle employed to facilitate the fulfilment of student migration intentions. With a shift from the classical economic models of understanding the decision to migrate, this article elucidates the fears, anxiety, joys and perplexities that are embedded in the thought of student migration.